Canadian Public Library Pandemic Response: Bridging the Digital Divide and Preparing for Future Pandemics - Intahchomphoo, Channarong; Vellino, André (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This article examines the impact of the COVID-19 pandemic on computer and Internet access services in Canadian public libraries as well as the implications of this lack of access for people facing socioeconomic barriers, and how Canadian public libraries could address digital divide issues in the post-pandemic era. Recommendations on future pandemic preparedness for public libraries are also discussed in this article. This research project conducted a bilingual (English and French) online survey targeting public library technicians, librarians, and library board members across Canada. From 1,631 research invitation emails sent to public library staff across Canada and three Facebook posts on Canadian public library staff groups, over a one-year period from November 3, 2021, to November 6, 2022. 226 individuals participated in the online survey questionnaire. Findings suggest that the COVID-19 pandemic has exacerbated social inequalities in Canada, including access to computers and the Internet. The digital divide could lead to poor health outcomes and put existing disadvantaged populations at greater risk in terms of future employment opportunities. The digital divide needs to be addressed so that Canadians in low-income households and those living with disabilities do not get left behind. Importantly, public libraries in Canada have been working tirelessly to equalize access to computers, the Internet, and digital literacy training and support. Their determination, social responsibility, and professional ethics need to be acknowledged. Finally, this article's recommendations for future pandemic preparedness in Canadian public libraries may also be applicable and beneficial to public libraries globally.